Artificial Intelligence (AI) In Pakistani Newsrooms: Examining the Adoption and Impact of Artificial Intelligence in Dawn, Jang, and Express Newspapers - Zamir, Ahmed; Ahmed, Maqsood (Journal of Peace, Development and Communication, 2024)
Abstract Artificial intelligence (AI) improves productivity, stimulates creativity, and makes it possible to solve challenging issues in various industries, including banking, transportation, healthcare, and media. Artificial Intelligence(AI) plays a revolutionary role in the media industry by automating repetitive tasks, personalizing user experiences, and streamlining content creation. With AI tools, journalists can easily evaluate sizable data sets, spot trends, and produce insights that can result in more thorough and accurate reporting. The primary objective of this study was to examine the impact of artificial intelligence (AI) technology on the media industry in Pakistan. The study specifically aimed to investigate the role of artificial intelligence and how journalists in Pakistan perceive its potential as a tool to enhance reporting capabilities. This study is designed to examine the impact of artificial intelligence on Pakistani media and its applications in news production, content curation, and audience engagement. The study employed a unique and rigorous research methodology, utilizing purposive sampling techniques to select 150 participants journalists from the three prominent daily Newspapers of Pakistan: Dawn, Jang, and Express. The study's significant findings underscore the profound impact of AI technology on the media industry in Pakistan. However, understanding the challenges is critical to ensuring the successful integration of AI into the media industry. Mechanisms like metadata analysis and track-back systems should be implemented to ensure that content is published. The study recommends addressing the challenges related to AI adoption by ensuring government and organizational support. Finally, media practitioners and regulators should enhance awareness of AI benefits among all stakeholders in the media and communication sectors. KEYWORDS: Media, Communication, Artificial intelligence, Journalist, Newsroom.